2015
DOI: 10.1021/acs.energyfuels.5b00790
|View full text |Cite
|
Sign up to set email alerts
|

Co-combustion of Agricultural Straw with Municipal Sewage Sludge in a Fluidized Bed: Role of Phosphorus in Potassium Behavior

Abstract: The influence of municipal sewage sludge addition on the agglomeration characteristic during straw combustion in a fluidized bed was investigated in a bubbling fluidized-bed reactor (5 kW th ) with quartz sand as the bed material. In addition, chemical reactions between the alkali metal and three kinds of phosphorus-containing model compounds were studied to investigate the effect of phosphorus on the behavior of the alkali metal during wheat straw combustion. The element contents, the crystalline phases, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Because of the excessive consumption and nonrenewability of traditional energy sources, energy security is deemed as an important element affecting social and economic development. Currently, most combustion studies are based on conventional straw‐based biomass . It is easy to ignore that unconventional biomass (shell‐based biomass) is a promising fuel that provides thermal energy .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the excessive consumption and nonrenewability of traditional energy sources, energy security is deemed as an important element affecting social and economic development. Currently, most combustion studies are based on conventional straw‐based biomass . It is easy to ignore that unconventional biomass (shell‐based biomass) is a promising fuel that provides thermal energy .…”
Section: Introductionmentioning
confidence: 99%
“…The Ca and Mg compounds in CS can provide reactive chemical sites for phosphorus to form Ca 18 Mg 2 H 2 (PO 4 ) 14 and Ca 2 P 2 O 7 . Ren et al [53] also found that sewage sludge co-combustion with wheat straw leads to the formation of alkali-rich phosphate silicate that restrains the reaction between the alkali and quartz. Reactions between the P-rich additive and alkali metal lead to the formation of K-Ca-P compounds.…”
Section: Incinerationmentioning
confidence: 99%
“…As shown in Table 2, the contents of P 2 O 5 , CaO, and K 2 O of the fuel blend with 50 wt % CP are higher than those of the other two fuel blends. The reaction between P and alkali metals such as K and Ca in biowastes during the combustion leads to the formation of stable K–Ca–P compounds with a high melting temperature, which is beneficial for reducing the volatilization of P and the formation of particulate matter, thereby increasing the P enrichment efficiency in the bottom ash. , Thus, CP is more effective on the enrichment of phosphorus in ash than RH and SSt.…”
Section: Resultsmentioning
confidence: 99%
“…), may also promote P transformation during thermal treatment. Studies have investigated the incineration of sewage sludge mixed with cotton stalks or wheat straw to improve the P bioavailability of fly ash. , However, few studies have investigated the speciation evolution of P during low-temperature co-combustion of sewage sludge with biowaste. The speciation (e.g., physical distribution and the chemical state) of an element is well known to affect its transport, mobility, and availability.…”
Section: Introductionmentioning
confidence: 99%